ANALISIS KEMAMPUAN MEMBACA PUISI MELALUI EKSPRESI PADA SISWA KELAS III SD - yuhanita ulzana, Yuhanita Ulzana; Daroe Iswatiningsih; Annisah Nurul Dzulaekha; Rina Dwi Astuti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Reading poetry is an activity of reading literary works that requires expressive skills such as intonation, articulation, facial expression, and body movement to convey its meaning accurately. However, elementary school students often read poetry mechanically, which diminishes artistic expression and emotional engagement. This study employs a qualitative approach with a descriptive study design to analyze the expressive reading abilities of third-grade students at Muhammadiyah 4 Batu Elementary School. Interviews, observations, and teacher documentation were used to collect data. The results show that students experienced improvement in expressive poetry reading. Teachers implemented strategies to enhance students’ ability to read poetry effectively, including structured learning activities that supported students in expressing themselves and provided reading models.